Customary assets conflict and their impact on social relations fragmentations - Bayu Adhinata (Masyarakat, Kebudayaan dan Politik, 2020)
This research focuses on studying conflicts involving traditional villages in fighting over the ownership status of the Temple of Death (Pura Dalem) as an asset that must be owned by a traditional village. Conflict involving two traditional villages in Bali, namely Kemoning and Budaga Village in Klungkung, resulted from a claim of ownership by one of the parties ahead of a massive celebration tribute to this temple’s birth centuries ago. The ownership claim led to rejection from another party, who said their traditional village was also entitled to the Temple of Death. This mutual ownership claim then escalated into an open conflict that resulted in casualties and injuries between the two parties. This research seeks to outline the root problems of this conflict and describe the actors, dynamics, and impacts of the conflict. This study used a qualitative approach through in-depth interviews with five informants consisting of two key informants (former heads of the Kemoning and Budaga Villages), one Klungkung resort police officer, and two people Kemoning and Budaga Village residents. Moore, Mitchell, Furlong, and Kriesberg use several perspectives to analyze the social conflict. The results showed that the problem of the two traditional villages lies in the inaccuracy of historical data, besides that there are different perspectives between the two parties about the existence of this temple, excessive control, and dominance in the management and poor communication caused the emergence of a hostile relationship pattern, raising mutual claims over the ownership of this Temple of Death. The dispute that led to this clash created an increasingly tenuous relationship between the two traditional villages.